Analysis on Unemployment and Inflation in Indonesia for The Periode of 1980 -2016 using Philipps Curve Approach - Ruchba, Sarastri Mumpuni; Hadiyan, Fakhry (Proceeding UII-ICABE, 2020)
This research was carried out using annual report data on the employment level and Consumer Price Index obtained from Indonesian Statistics Book of 1980-2016 published by Central Bureau of Statistics (BPS, Ind) aimed to look into the relationship between unemployment and inflation in Indonesia in the period of year 1980 – 2016. The analysis method used is Vector Error Correction Model (VECM), which is a restricted VAR model, because of the existing cointegration that presented the long period relationship between the unemployment and inflation variable rate in VAR model. VECM could analyse the long and short period inter variable relationship. The result of the analysis showed the significant presence of negative relationship with the IHK within the short period of the lag 2 unemployment variable rate. Hence, within three years (lag 3) the IHK variable and the unemployment rate significantly affected each other with a positive relationshipship. In the long period, the unemployment rate variable had a positive influence to the IHK variable. Furthermore, the Impluse Response Function (IRF) explained the effect of the shock on one variable towards another variable. At the first to the second period the IHK variable had not responded to the given shock, while it experienced a negative decrease in the third period. At the fourth period the IHK variable responded towards the positive, and then the trend pointed out at a positive realationship until the tenth period. Keywords: Phillips Curve, Unemployment Rate, Inflation, Consumer Price Index, Vector Error Correction Model (VECM).